Digital marketing plays the vital role to fulfill customer satisfaction: A study on Analyzen Bangladesh Ltd. - Khan, Nusrat Jahan (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.